Effect of Polycondensation Reaction Conditions on the Properties of Thermotropic Liquid‐Crystalline Copolyester - Yikici, Meryem; Yerlikaya, Zekeriya; Aksoy, Serpil; Altinok, Haydar (Informa UK Limited, 2008)
In this study a range of wholly aromatic copolyesters based on kink m‐acetoxybenzoic acid (m‐ABA) monomer (33 mol%) and equimolar‐linear p‐acetoxybenzoic acid (p‐ABA), hydroquinone diacetate (HQDA) and terephthalic acid (TPA) monomers (67 mol%) have been synthesized by melt polycondensation reaction process at 280°C and 260°C for different time intervals. Characterization of copolyesters were performed by solution viscosity measurement, wide–angle X‐ray diffraction (WAXD), differential scanning calorimetry (DSC), hot‐stage polarized light microscopy, proton‐nuclear magnetic resonance analysis (1H‐NMR). According to the results obtained, copolyesters showed thermotropic liquid crystalline behavior in an appropriate temperature range. The copolyesters were prepared in high yields. It was observed that the intrinsic viscosities of the copolyesters are increased regularly with increasing polymerization time and temperature. All the copolyesters were soluble in a trifluoroacetic acid/dichloromethane (30:70 v/v...
Keywords: copolyester; melt spinning; liquid crystalline; thermotropic; polycondensation; fiber